Microsoft 365 Endpoint Administrator Associate (MD-102) Cert Prep: 2 Manage Identity and Compliance. - Warren, Andrew; Press, Microsoft (linkedin.com, 2023)
Prepare for the MD-102 Endpoint Administrator exam and learn to manage devices and client applications more effectively, with a focus on managing identity and compliance.